2016
DOI: 10.1039/c6ra04604e
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous adsorption of fluoride and hexavalent chromium by synthetic mesoporous alumina: performance and interaction mechanism

Abstract: Combined pollution by fluoride (F−) and hexavalent chromium (Cr(vi)) in water bodies causes much environmental concern and its treatment is of the utmost importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
1
15
1
Order By: Relevance
“…In the previous study, carried out in individual (simple) systems for Cr(VI) and F − separately (Romar-Gasalla et al [13]), the highest F − adsorption corresponded to forest soil, pyritic material, pine bark, and oak ash, with values between 30 and 40 mmol kg −1 , which represented between 60-72% of the highest concentration of F − added, while pine bark, pine sawdust, and pyritic material showed the highest adsorption of Cr(VI) for the highest concentration of Cr(VI) added, with 69, 40, and 32 mmol kg −1 , representing 98, 68, and 55%, respectively. Li et al [2] found higher affinity for F − than for Cr(VI) in synthetic alumina gels, while Mohapatra et al [38] obtained the opposite result in alumina nanofibers. The behavior observed in the present study can be related to the different composition of the sorbent materials used, and to their pH values (Table S1, Supplementary Material).…”
Section: F − and Cr(vi) Competitive Adsorption In A Binary Systemmentioning
confidence: 98%
See 4 more Smart Citations
“…In the previous study, carried out in individual (simple) systems for Cr(VI) and F − separately (Romar-Gasalla et al [13]), the highest F − adsorption corresponded to forest soil, pyritic material, pine bark, and oak ash, with values between 30 and 40 mmol kg −1 , which represented between 60-72% of the highest concentration of F − added, while pine bark, pine sawdust, and pyritic material showed the highest adsorption of Cr(VI) for the highest concentration of Cr(VI) added, with 69, 40, and 32 mmol kg −1 , representing 98, 68, and 55%, respectively. Li et al [2] found higher affinity for F − than for Cr(VI) in synthetic alumina gels, while Mohapatra et al [38] obtained the opposite result in alumina nanofibers. The behavior observed in the present study can be related to the different composition of the sorbent materials used, and to their pH values (Table S1, Supplementary Material).…”
Section: F − and Cr(vi) Competitive Adsorption In A Binary Systemmentioning
confidence: 98%
“…Li et al [2] found for synthetic alumina gels that the coexistence of F − and Cr(VI) in solution decreased Cr(VI) adsorption, but enhanced F − adsorption, due to the fact that alumina has higher affinity for F − than for Cr(VI), and Cr can form ≡CrOH 2 + groups, which could be new adsorption sites for F − . Deng et al [48], studying competitive adsorption in fibers impregnated with cerium, found that F − adsorption increased in a binary system in relation to a simple system, whereas Cr(VI) adsorption decreased (i.e., Cr(VI) favored F − adsorption, but F − hindered Cr(VI) adsorption).…”
Section: F − and Cr(vi) Competitive Adsorption In A Binary Systemmentioning
confidence: 99%
See 3 more Smart Citations